2014
DOI: 10.1007/s10534-014-9743-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug repositioning: auranofin as a prospective antimicrobial agent for the treatment of severe staphylococcal infections

Abstract: Auranofin, (AF), a gold(I) complex in clinical use for the therapy of rheumatoid arthritis, is reported here to produce remarkable bactericidal effects in vitro against Staphylococcus sp. Noticeably, a similar antimicrobial action and potency are also noticed toward a few methicillin-resistant Staphylococcus aureus strains but not toward Escherichia coli. The time and concentration dependencies of the antimicrobial actions of AF have been characterized through recording time kill curves, and a concentration de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 17 publications
(15 reference statements)
11
51
0
Order By: Relevance
“…Another drug, auranofin, has recently been reported to have strong antimicrobial activity against several Gram-positive organisms (15)(16)(17), and our results agree well with these reports, as the IC 50 of auranofin was well below the lowest concentration tested (0.6 M).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Another drug, auranofin, has recently been reported to have strong antimicrobial activity against several Gram-positive organisms (15)(16)(17), and our results agree well with these reports, as the IC 50 of auranofin was well below the lowest concentration tested (0.6 M).…”
Section: Resultssupporting
confidence: 93%
“…Auranofin is a gold thiolate compound that has been used to treat rheumatoid arthritis for decades, and it has recently received significant attention due to its antimicrobial potential. A typical dosage for arthritis treatment is 6 mg per day, and the peak plasma concentration after 2 h is 0.025 g/ml; the steadystate blood concentration of gold is 3.5 M. In two separate studies, Hokai et al (15) and Cassetta et al (16) discovered that auranofin significantly inhibits the growth of S. aureus USA300, and they found MICs of 0.2 g/ml and 0.25 g/ml, respectively (ϳ0.3 M). Recently, Siles et al (6) showed that auranofin can inhibit the growth and the formation of Candida albicans biofilms.…”
Section: Resultsmentioning
confidence: 99%
“…Auranofin showed potent growth inhibition against each of the Gram-positive strains tested ( Table 1). The activities against S. aureus are consistent with recent findings of auranofin's antimicrobial activity against drug-sensitive and methicillin-resistant strains of S. aureus (24,25). In addition, we found that auranofin inhibits growth of Enterococcus faecium and Enterococcus faecalis, with an MIC of 0.5 mg/L for both.…”
Section: Resultssupporting
confidence: 91%
“…Auranofin has been shown to inhibit S. aureus [21,29], Mycobatcerium tuberculosis [29] and the parasites Schistosoma mansoni, Entamaeba histolytica and Giardia lamblia have also demonstrated susceptibility to auranofin, both in vitro and in vivo [23,24,30]. The platyhelminth Echinococcus granulosus are susceptible to auranofin, inhibiting larval worms at 2.5 μM in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Since the antistaphylococcal activity of auranofin has been described [21], we investigated some of the most medically relevant pathogens, testing the ESKAPE bacterial pathogens (E. faecium, S. aureus, K. pneumoniae, A. baumannii, P. aeruginosa and Enterobacter) for susceptibility to auranofin. We found that auranofin was able to inhibit S. aureus and E. faecium and A. baumannii, affecting both Gram-positive and a Gramnegative bacteria.…”
Section: Antibacterial Activity Of Auranofinmentioning
confidence: 99%